KEPEMILIKAN ASING DAN KEPEMILIKAN PUBLIK TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA SEKTOR TRANSPORTASI (Studi Pada Emiten Transportasi Di BEI) - Roma R. Siburian; Makhdalena Makhdalena; R.M Riadi R.M Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Research on foreign ownership, public ownership and company value has been done by many previous researcher, but the result has not been consistent, that some have influence and some have no influence. Thus, researchers are interested in re-examining foreign ownership, public ownership and corporate value. The purpose of this study is to examine and analyze the effect of foreign ownership, public ownership and corporate value. The population of this study is a transport sector company listed on the Indonesia Stock Exchange which has complete data on foreign ownership, public ownership and corporate value for four consecutive years 2013-2016. The type of data from this research variable is secondary data obtained by documentation technique that comes from Indonesian stock exchange website (www.idx.co.id). Methods of data analysis using regression.The result of the research shows that foreign ownership and public ownership influence simultaneously and partially to company value.Keywords: foreign ownership, public ownership, corporate value